Sosialisasi Standar Akuntansi Keuangan EMKM pada Guru-Guru Akuntansi Sekolah Menengah Kejuruan di Kabupaten Rokan Hilir - Taufeni Taufik; Yuneita Anisma; Yusralaini Yusralaini (Asosiasi Dosen Akuntansi Indonesia, 2020)
The purpose of the activity is to provide an understanding of financial reporting from cash to accrual basis to micro and small entrepreneurs in the Menpura sub-district, Siak Regency, in accordance with financial accounting standards for micro, small and medium entities which are effective in 2017 and come into effect in 2018. by socializing the Financial Accounting Standards for Small, Micro and Medium Entities, it is carried out by providing training to teachers of accounting subjects at Vocational High Schools in Rokan Hilir Regency. All participants were given an explanation of the financial accounting standards for Micro, Small and Medium Entities, which were effective as of January 1, 2018. Then there was a question and answer session with the participants. Finally, an evaluation was carried out by conducting a post test to see the teachers' understanding of the accounting standards for small and middle micro entities.